Membangun Karakter Pribadi Menuju Sukses - Suharnan, ' (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. Many people want to achieve success. Unfortunately, in reality success is never achieved overnight. To become successful, a person needs some qualities of personal characteristics as well as human capital for success. There for, this article intends to discuss what is success, the personality characteristics of successful people, and how developing these qualities toward success in our carrier and life.Keywords: success, characteristics of successful person, self-development